Instagram usage in destination branding through sports event: Study of Mandalika 2021 World Superbike - Prastya, Narayana Mahendra; Maharani, Baiq Muthia; Ningsih, Ida Nuraini Dewi Kodrat (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
International sports events can be utilized by the host city or region to form destination branding. Social media become the important tools for branding activities. This article aims to analyze the social media, focus on Instagram usage in Mandalika destination branding through the 2021 World Superbike (WSBK) sports event. WSBK 2021 become the first world-class race event held in Mandalika, and there are a number of other negative issues ahead of WSBK 2021. This research uses a qualitative method with primary data is interviews with representatives from the Indonesia Tourism Development Corporation (ITDC). Research results shows ITDC use Instagram @itdc_id as the main platform to promote Mandalika to form destination branding. The theme of content uploaded on @itdc_id are about tourist attractions in Mandalika and information about circuit readiness. ITDC regulates Instagram uploads for weekdays are spots that can be used for sports activities, while for weekends information about WSBK races, for example regarding circuit readiness or rules for spectators. During the series of race days, ITDC didn't even upload content related to the races in order to avoid copyright issues. Based on secondary data from observation towards ITDC’s Instagram posted and Google Trends analytics shows the internet user pay lower attention to the sport tourism theme. Internet users more interested in race-related information.